Pregnancy outcome in afibrinogenemia: Are we giving enough fibrinogen concentrate? A case series. Issue 2 (22nd January 2020) - Saes, Joline L.; Laros‐van Gorkom, Britta A. P.; Coppens, Michiel; Schols, Saskia E. M.
Abstract: Congenital afibrinogenemia is a rare autosomal recessive disorder associated with an increased risk of hemorrhage, thrombosis, and obstetric complications. This case series of 4 pregnancies in 2 related patients seeks to address the key clinical question of the necessary doses of fibrinogen concentrate during pregnancy and puerperium. One pregnancy without the prophylactic use of fibrinogen concentrate resulted in spontaneous abortion. The second pregnancy was complicated by a subchorionic hematoma despite the prophylactic administration of fibrinogen concentrate to maintain the plasma trough levels at ≥0.6 g/L. Labor was complicated by postpartum hemorrhage with a blood loss volume of 1480 cc. Two weeks later, the patient presented with postpartum thrombosis. The other 2 pregnancies were uncomplicated with fibrinogen trough levels ≥1.0 g/L during pregnancy and ≥1.5 g/L during labor. These cases illustrate that during pregnancy, patients may benefit from fibrinogen trough levels ≥1.0 g/L. In addition, the increased risk of postpartum thrombosis with prolonged fibrinogen supplementation warrants personalized postpartum advice that is guided by postpartum blood loss.